Lanthanum Carbonate Modulates Inflammatory Profile in Hemodialysis Patients: Relationship with Fibroblast Growth Factor-23 - J.F. Navarro-González (European Journal of Inflammation, 2013)
Elevated fibroblast growth factor 23 (FGF-23) is independently associated with increased inflammatory markers in chronic kidney disease. Lanthanum carbonate (LaCa) reduces FGF-23. We studied the effects of LaCa on inflammatory profile of hemodialysis patients, and the relationship with changes in FGF-23. This prospective study was performed under habitual clinical practice conditions. Twenty-six hemodialysis patients with serum phosphate > 5 mg/dl receiving calcium-based phosphate binders were switched to LaCa. Ten patients with phosphate ≤ 5 mg/dl under calcium-based phosphate binders were enrolled as a control group for comparison. Serum calcium, phosphorus, calcium-phosphate product (CaxP), intact parathyroid hormone and the inflammatory profile [including serum high-sensitivity C-reactive protein (hs-CRP), tumor necrosis factor-α (TNF-α), interleukin (IL)-6 and IL-10, as well as mRNA expression levels of TNF-α and IL-6 in peripheral blood mononuclear cells] were analyzed. Serum FGF-23 significantly decreased in patients switched to LaCa (P< 0.01), with a concomitant reduction in serum hsCRP (-10.9%, P < 0.01), TNF-α (-6.7%, P < 0.05) and IL-6 (-8.1%, P < 0.01). mRNA expression levels of TNF-α and IL-6 in PBMC also decreased by 7.8% (P< 0.05) and 10.3% (P< 0.01), respectively. Multivariate regression analysis demonstrated that variations in FGF-23 were the only independent determinant of the changes in serum and mRNA expression levels of inflammatory parameters. In conclusion, LaCa posses anti-inflammatory actions, which are significant and independently associated with the reduction of FGF-23. FGF-23 may regulate inflammatory cytokine gene expression at the transcriptional level. Whether these effects have influence on clinical outcomes warrants consideration.